2017
DOI: 10.1093/jac/dkx405
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiology and antimicrobial resistance of Neisseria gonorrhoeae in New Zealand

Abstract: BackgroundAntimicrobial-resistant Neisseria gonorrhoeae is a major threat to public health. No studies to date have examined the genomic epidemiology of gonorrhoea in the Western Pacific Region, where the incidence of gonorrhoea is particularly high.MethodsA population-level study of N. gonorrhoeae in New Zealand (October 2014 to May 2015). Comprehensive susceptibility testing and WGS data were obtained for 398 isolates. Relatedness was inferred using phylogenetic trees, and pairwise core SNPs. Mutations and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 51 publications
5
70
0
1
Order By: Relevance
“…Raw sequence reads are available on NCBI under Bioproject accession number PRJNA430457. Reads were quality-checked, trimmed and assembled using the Nullarbor pipeline v.1.20 (available at: https://github.com/tseemann/nullarbor), as previously described [60], but with the exception of the assembly step which was performed using Shovill (available at: https://github.com/tseemann/shovill), a genome assembler pipeline wrapped around SPAdes v.3.9.0 [61] which includes post-assembly correction. Assemblies were also reordered against reference strain K. pneumoniae 30660/NJST258_1 (accession number CP006923) using progressive Mauve v.2.4.0 [62] prior to annotation with Prokka [63] and screened for antibiotic resistance genes using Abricate v.0.6 (available at: https://github.com/tseemann/abricate).…”
Section: Methodsmentioning
confidence: 99%
“…Raw sequence reads are available on NCBI under Bioproject accession number PRJNA430457. Reads were quality-checked, trimmed and assembled using the Nullarbor pipeline v.1.20 (available at: https://github.com/tseemann/nullarbor), as previously described [60], but with the exception of the assembly step which was performed using Shovill (available at: https://github.com/tseemann/shovill), a genome assembler pipeline wrapped around SPAdes v.3.9.0 [61] which includes post-assembly correction. Assemblies were also reordered against reference strain K. pneumoniae 30660/NJST258_1 (accession number CP006923) using progressive Mauve v.2.4.0 [62] prior to annotation with Prokka [63] and screened for antibiotic resistance genes using Abricate v.0.6 (available at: https://github.com/tseemann/abricate).…”
Section: Methodsmentioning
confidence: 99%
“…In the United States, lineages with reduced susceptibility to cefixime were found to be primarily circulating among MSM, and transmission from MSM to men who have sex with women (MSW) occurred more often than MSW to MSM transmission . WGS of N. gonorrhoeae populations in New Zealand shows that the majority of clusters contain isolates from both men and women, suggesting the absence of clones associated with exclusively MSM transmission . While the N. gonorrhoeae global population does not show geographic structure, examining WGS of isolates from smaller scales (i.e., London) shows that transmission links are associated with shorter geographic distances .…”
Section: Genomic Epidemiology Approaches To Reducing the Transmissionmentioning
confidence: 99%
“…Population structure analyses based on Bayesian methods have identified 5-12 clusters in N. gonorrhoeae populations, depending on the data set, and these clusters and major clades defined by phylogenetic analysis have little to no geographic structure. [21][22][23][24] In N. meningitidis, clade-specific restriction modification systems, competition between lineages, and selection by the immune system contribute to the population structure, 25,26 but the factors that maintain population structure in N. gonorrhoeae have not been identified. The global distribution of these major groups suggests that international transmission of N. gonorrhoeae is relatively common.…”
Section: Global Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlating the phenotypic susceptibility and resistance of a bacterial isolate to a WGS genotype also needs to be performed on an organism-by-organism basis. Recent studies have empirically demonstrated that predicting susceptibility and resistance using WGS data is feasible or potentially feasible for S. aureus (13)(14)(15), Enterobacteriaceae (22)(23)(24)(25), Pseudomonas aeruginosa (26,27), Campylobacter (28), Helicobacter pylori (29), Neisseria gonorrhoeae (30,31), and Mycobacterium tuberculosis (13,18,(32)(33)(34)(35). In one of these studies, WGS data from more than 1,700 isolates of Salmonella enterica were used to predict susceptibility and resistance to 13 antimicrobial agents (22).…”
Section: Barriers To High-throughput Sequencingmentioning
confidence: 99%